2019
DOI: 10.1017/s0033291719002113
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relationships among psychopathology, premorbid adjustment, cognition and psychosocial functioning in first-episode psychosis: a network analysis approach

Abstract: BackgroundBetter understanding of interplay among symptoms, cognition and functioning in first-episode psychosis (FEP) is crucial to promoting functional recovery. Network analysis is a promising data-driven approach to elucidating complex interactions among psychopathological variables in psychosis, but has not been applied in FEP.MethodThis study employed network analysis to examine inter-relationships among a wide array of variables encompassing psychopathology, premorbid and onset characteristics, cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 86 publications
(113 reference statements)
5
24
0
Order By: Relevance
“…In case of "difficulty in abstract thinking" (PANSS-N5) that had been considered either as a negative (Kay et al, 1987) or a cognitive-disorganized symptom (Vignapiano et al, 2019;Wallwork et al, 2012), with PS&B, a completely different cluster was suggested. This placement, however, is in line with the close connection between difficulty in abstract thinking and disorganization of the PANSS reported for male patients with schizophrenia-spectrum disorders (van Rooijen et al, 2018), the close association between disorganized and cognitive-perceptual symptoms in a study of schizotypal personality traits in the general population (Dodell-Feder et al, 2019) and between PANSS positive and disorganization total scores in first-episode psychosis and schizophrenia (Chang et al, 2019;Galderisi et al, 2020). However, its placement is challenged by a recent network analysis including neurocognitive and PANSS measures (Moura et al, 2021) in which "difficulty in abstract thinking" (PANSS-N5) was the only PANSS item integrated in the neurocognitive domain.…”
Section: Tablesupporting
confidence: 79%
“…In case of "difficulty in abstract thinking" (PANSS-N5) that had been considered either as a negative (Kay et al, 1987) or a cognitive-disorganized symptom (Vignapiano et al, 2019;Wallwork et al, 2012), with PS&B, a completely different cluster was suggested. This placement, however, is in line with the close connection between difficulty in abstract thinking and disorganization of the PANSS reported for male patients with schizophrenia-spectrum disorders (van Rooijen et al, 2018), the close association between disorganized and cognitive-perceptual symptoms in a study of schizotypal personality traits in the general population (Dodell-Feder et al, 2019) and between PANSS positive and disorganization total scores in first-episode psychosis and schizophrenia (Chang et al, 2019;Galderisi et al, 2020). However, its placement is challenged by a recent network analysis including neurocognitive and PANSS measures (Moura et al, 2021) in which "difficulty in abstract thinking" (PANSS-N5) was the only PANSS item integrated in the neurocognitive domain.…”
Section: Tablesupporting
confidence: 79%
“…61 The fact that 2 of the 3 strongest bridge strength centrality nodes belonged to the disorganization community (G11 and G12) reiterates the pivoting role this community plays between psychopathology and cognition in line with findings from previous network analysis studies, including on high-risk subjects. 17,19,52 A second set of bridging nodes was related to the "affective" components of the network and had "suspiciousness" as the hub, mostly binding positive symptoms, excitement, and emotional distress communities. This might indicate that suspiciousness is a bridge for the emergence of mood episodes within SSD.…”
Section: Small-worldness Index and Centrality Analysismentioning
confidence: 99%
“…Several cross-sectional studies used network analysis to investigate clinical variables in psychotic disorders [14][15][16] ; however, to our knowledge, only 3 included the combination of psychopathological (factor level) and cognitive symptoms. [17][18][19] Overall, no previous research looked simultaneously at psychopathology, cognition, and motor symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…As to the factor structure of negative symptoms in first episode samples, the sum score of selected items from PANSS believed to cover the subdomain of amotivation [184] have been used in two studies [185,186]. In line with this, few studies have used a suggested factor-structure from the SANS [187] to report on the severity of amotivation [188,189]. Several studies have reported specifically on each of the four SANS-subdomains, that is, Affective flattening, Alogia, Anhedonia/Asociality, and Avolition/Apathy [190][191][192][193].…”
Section: Assessment Of Negative Symptoms In First-episode Psychosis Pmentioning
confidence: 99%